A bibliometric analysis of green human resource management based on scopus platform - Muhammad Hamza Khan; Syaharizatul Noorizwan Muktar (Cogent Business & Management, 2020)
The increasing research in protecting the environment has led to the emergence of a new research paradigm in the field of human resource management (HRM). The HRM researchers are now exploring how HRM can contribute to green outcomes and invented the term "green human resource management" (GHRM). In this bibliometric analysis, 147 documents were examined on GHRM scholarship. The objective of this study was to analyze the volume, increasing trend, worldwide distribution, key journals, pioneer authors, dominating nations and dominating sectors in GHRM. For this work, six combinations of the words were merged together with logical operators, " TITLE-ABS-KEY ("green human resource management") OR TITLE-ABS-KEY ("green hr") OR TITLE-ABS-KEY ("green human resource") OR TITLE-ABS-KEY ("GHRM") OR TITLE-ABS-KEY ("green human resource management practices") OR TITLE-ABS-KEY ("GHRMP"), thus making the span broader. The review showed that the GHRM is still an emerging concept and this review hopes to guide modern researchers by giving an overview of the current situation.
Keywords: 650; green human resource management; sustainable development; bibliometric analysis; Scopus